The Statistical determinants of customer loyalty in microenterprises in the commercial sector - Escalante-Bourne, Teodoro Mauricio; Blum-Alcívar, Hilda Mercedes; Mosquera Yèpez, Gari Giovanni; Escalante-Ramírez, Teodoro Antonio (Revista Internacional de Estudios en Ciencias Administrativas STRATEGOS, 2026)
Customer loyalty is one of the most relevant factors for the sustainability and growth of microenterprises, especially in emerging economic contexts such as Ecuador. The objective of this study was to analyze the statistical determinants that influence customer loyalty in microenterprises in the commercial sector, considering variables such as customer satisfaction, perception of quality, perceived price, trust in the brand and frequency of repurchase. The research was developed under a quantitative approach, with a non-experimental design, descriptive and correlational type. The population was made up of 150 customers of commercial microenterprises, to whom a structured questionnaire based on the Likert scale was applied. For the analysis of the data, statistical techniques such as contingency tables, Chi-square test and logistic regression analysis were used, in order to identify significant relationships between the variables studied. The results show that customer satisfaction and brand trust have a statistically significant relationship with repurchase frequency, which indicates that these factors directly influence consumer loyalty. Likewise, it was identified that the perception of quality and the perceived price act as moderating variables in purchasing behavior. In conclusion, microenterprises that develop strategies focused on customer experience, product quality, and building trust can strengthen their consumer loyalty and improve their competitiveness in the local market.
Keywords: loyalty, customer, microenterprises, satisfaction, consumer